The Repercussion of the False Memories Syndrome in the Eyewitness Testimony: an Analysis of Decisions from the Rio Grande do Sul State Court - Flaviane Baldasso; Gustavo Noronha de Ávila (Revista Brasileira de Direito Processual Penal)
False memories are distortions of memory that can impact decisively on the evaluation of a criminal event of interest to the criminal system. Despite the growing interest in the subject, few empirical works have explored the practical consequences of the phenomenon. Along with, the question is if it is possible to measure the repercussion for our criminal proceedings, as well if the theses concerning false memories have been accepted by the Judiciary and in which cases. The present article intends to analyze the repercussion of the phenomenon of false memories, in terms of testimonial evidence, from 437 judgments of the Court of Justice of Rio Grande do Sul. Using the content analysis methodology of Lawrence Bardin, we explored the types of crimes in which the false memories argument has been used, if the hypothesis of this distortion has sensitized the judges, as well as if the analyzes of the judges have been supported in the bibliographical production on the psychology of the testimony. From the numbers raised, it was possible to perceive a considerable increase in the invocation of the argument of the False Memories, but this has not been reversed in the promotion of freedom in the scope of the gaucho penal process.